Legal basis for the interaction between local with state authorities - Abdulridha, Jaafar Naser; Hashim, Salwan Jaber; Sultanov, Evgeny Batirovich (Cuestiones Políticas, 2020)
The objective of the article is to analyze the legal basis for interaction between local and state authorities within the framework of the current constitution of the Republic of Iraq. At the methodological level, documentary observation was used. In recent years, after the transition to a new political regime in Iraq in 2003, many issues relating to local administrations and their interaction with state bodies have been identified and enshrined in the Constitution of the Republic of Iraq in 2005. Some of the most serious problems are the lack of a clear organization of relations between government bodies and local governments, the efficiency problems of the various authorities, as well as the lack of flexible solutions in legislation and the Constitution. The need to solve these problems is often manifested at all levels. At the same time, we find no real decisions that do not cause popular discontent in all Iraqi provinces, especially in Basra province. It is concluded that relations between regional and national authorities are mediated by the presence of bureaucracy, financial and administrative corruption administrative and political conflicts between political parties.